INFORMATION TECHNOLOGY AND PRODUCT DESIGN ON CONSUMER INTEREST IN PECI RENCONG ACEH PRODUCTS IN JUANG BIREUEN CITY - Ismayli; Khalil Gibran; Usman Boini; Zulyaden Jayus (stiatabalong.ac.id, 2024)
Information technology and product design significantly impact consumer buying interest in Peci Rencong Aceh products in Juang Bireuen City. Information technology refers to the use of hardware and software to perform various data processing tasks, including capturing, transmitting, storing, retrieving, manipulating, and displaying information. Product design, on the other hand, is a key element that attracts consumers to products. This study aims to determine the influence of online promotion and customer satisfaction on purchase decisions. The sample size for this study was 100 participants, with data collected through questionnaires and analysed using multiple linear regression. The study found that a 1 percent increase in the information technology variable (X1) led to a 0.876 percent increase in consumer interest, assuming the product design (X2) remained constant. Conversely, a 1 percent increase in product design (X2) resulted in a 0.542 percent increase in consumer interest, assuming the information technology variable (X1) was constant. The correlation coefficient (R) of 81.8% indicates a strong relationship between information technology (X1), product design (X2), and consumer interest (Y). The influence of product design on consumer interest was found to be significant at 65.7% (p = 0.000). The T-test results showed that the T-count value exceeded the T-table value. Additionally, the F-test revealed an F-count of 86.612, compared to an F-table value of 2.31 at a 5% confidence level, leading to the acceptance of the Ha hypothesis and the rejection of the Ho hypothesis. The research concluded that both information technology and product design significantly influence consumer interest. Keywords: Information Technology, Product Design, Consumer Interest.